Penggunaan Musala sebagai Tempat Iktikaf Wanita (Studi pada Asrama Putri STIBA Makassar) - Siti Sa'dianti; Akrama Hatta; Aswin Aswin (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
This research aims to find out and understand the use of the STIBA Makassar women's dormitory prayer room as a place for women's iktikaf. The problems raised in the research are; First, what is the phenomenon of using the STIBA Makassar women's dormitory prayer room as a place of itikaf; and Second, what is the law regarding the use of the STIBA Makassar women's dormitory prayer room as a place of iktikaf for women. This type of research is descriptive qualitative with data collection methods through field research using a normative approach, phenomenological approach and conceptual approach. The research results are as follows; First, the phenomenon of using the STIBA Makassar women's dormitory prayer room as a place for women's iktikaf in terms of facilities is very feasible, but according to Sharia it still needs discussion; and Second, the law uses the STIBA Makassar women's dormitory prayer room as a place of iktikaf, namely: Jumhur ulama rejects its validity, Ḥanafiyyah says it is afdal, and STIBA Makassar does not allow it.